Felix G. Nakielny operating two-roll mill in Hercules Experimental Plastics laboratory - Hercules Incorporated (1945)
General view of employee Felix G. Nakielny operating a two-roll mill in the Experimental Plastics laboratory at the Hercules Powder Company plant in Parlin, New Jersey. According to the caption that accompanied this photograph in the March 1945 edition of The Hercules Mixer, Nakielny is working with a laboratory scale batch of molding powder used at the plant for testing purposes. The Parlin plant commonly produced ethyl cellulose, nitrocellulose and cellulose acetate, which were purchased by a variety of public and private industries as a raw material for use in plastics, films, lacquers, and other materials. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Research, Industrial; Hercules Incorporated; Corporations; Cellulose; Machinery; Nakielny, Felix G.